1991
DOI: 10.1111/j.1365-2621.1991.tb04725.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Heat‐Induced Gels from Beef Skeletal, Heart, Lung and Spleen Protein Fractions

Abstract: help explain the effects of protein interactions on product texture and water-holding properties. The objective of our research was to evaluate gels produced from high ionic strength soluble (HIS) protein fractions alone and in combination with low ionic strength soluble (LIS) or insoluble (IN) protein fractions from beef skeletal, cardiac, lung and spleen tissues.ABSTRACT Gelation properties were evaluated on high ionic strength soluble (HIS) proteins alone and in combination with low ionic strength soluble (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Surimi production involves extensive washing of minced fish muscle to remove the soluble sarcoplasmic components and most lipids. Nuckles et al (1991) reported that washed beef heart, lung and spleen myofibrillar proteins formed self-support gels but both stress and strain (at failure) of the gels were less than those of skeletal myofibrillar gels. Monagle et al (1985) and Kenney et al (1992) showed that washed cardiac and skeletal muscle homogenates improved meat batter stability and textural attributes of restructured beef products, thus offering an alternative for increased utilization of animal byproducts.…”
Section: Introductionmentioning
confidence: 97%
“…Surimi production involves extensive washing of minced fish muscle to remove the soluble sarcoplasmic components and most lipids. Nuckles et al (1991) reported that washed beef heart, lung and spleen myofibrillar proteins formed self-support gels but both stress and strain (at failure) of the gels were less than those of skeletal myofibrillar gels. Monagle et al (1985) and Kenney et al (1992) showed that washed cardiac and skeletal muscle homogenates improved meat batter stability and textural attributes of restructured beef products, thus offering an alternative for increased utilization of animal byproducts.…”
Section: Introductionmentioning
confidence: 97%
“…1990). Nuckles et al. (1991) reported that LIS proteins might have interfered with the matrix formation of HIS proteins, leading to decreases in apparent stress at failure and water holding ability.…”
Section: Resultsmentioning
confidence: 99%
“…(Dickinson 1999). Offal had a lower gel strength than skeletal muscles, because their total proteins contain lower levels of HIS proteins (Nuckles et al. 1991; Kurt and Zorba 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations